The Effect of Inflation, Open Unemployment Rate, Farmer Exchange Rate, and Provincial Minimum Wage on Poverty in the 15 Poorest Provinces in Indonesia - Retno Ajeng Sugesti; Moneyzar Usman (International Journal of Economics, Business and Innovation Research, 2024)
This study examines how inflation, open unemployment rate, farmer’s exchange rate, and provincial minimum wage affect poverty in 15 poorest provinces in Indonesia. Poverty serves as a substitute for the dependent variable, with inflation, open unemployment rate, farmer’s exchange rate, and provincial minimum wage as independent variables. The 15 provinces covered by panel data are used in this investigation for the years 2010–2022. Throughout the investigation, panel data regression is adopted and Fixed Effect Model (FEM) is decided. As shown by the findings, inflation has a negative and insignificant effect, open unemployment rate has a positive and insignificant effect, farmer’s exchange rate has a negative and insignificant effect, and provincial minimum wage has a negative and significant effect. Taken together, inflation, open unemployment rate, farmer’s exchange rate, and provincial minimum wage collectively affect poverty in 15 poorest provinces in Indonesia.